Hematopoietic Stem Cell Transplantation for Severe Combined Immunodeficiency (SCID) - Haddad, Elie; Hoenig, Manfred (Frontiers in Pediatrics, 2019)
Severe Combined Immunodeficiencies (SCID) are a heterogeneous group of monogenetic diseases. We describe the typical clinical presentation of patients with SCID as well as basic principles in diagnosis and therapy by hematopoietic stem cell transplantation. Therapeutic strategies may differ between subtypes and the inherently reduced capacity or inablility to reject a graft have to be considered.